Impact of assertive training on violent behavior reduction in psychiatric patients: A case study approach - Damayanti, Lelyana Septia (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Violent behavior is a condition where a person vent their feelings and anger in a physical form that can harm themselves, others and the environment. One of the nursing interventions that can be given patients with violent behavior is assertive training. The purpose of this study was to determine changes in the level of violent behavior through assertive training. Methods: The research design used is descriptive observational with case studies. The sample is Mr. M with a diagnosis of violent behavior who was treated at RSJ. Radjiman Wediodiningrat Lawang. The inclusion criteria in this study were patients with violent behavior problems, patients who were able to communicate well, patients who had completed at least SP1, while the exclusion criteria were patients refusing to be managed patients, patients who were getting mechanical restraints. Nursing interventions carried out are doing SP1-SP5 and doing assertive exercises in sessions 1-4. Findings: The findings of the intervention obtained patients can find out the causes of anger, identify unmet wants and needs, communicate the causes of anger, express verbal refusal, reject irrational requests. Conclusions: Assertive training teaches patients to train interpersonal communication skills, in conveying their needs, rights, without ignoring the rights of others so as to reduce violent behavior. This therapy is effective for reducing violent behavior and symptoms of patients with violent behavior. Novelty/Originality of this article: This study introduces assertive training as an effective non-pharmacological intervention to reduce violent behavior in psychiatric patients. It highlights how structured assertive exercises improve communication skills, enabling patients to manage anger and express needs appropriately.